The effectiveness of the electronic applications of mental arithmetic on the development of mathematical power with primary school students - Al Qassim, Khawla Abbas (Journal of Curriculum and Teaching Methodology, 2023)
The researcher aimed to identify effectiveness of electronic applications of mental arithmetic on the development of mathematical power among primary school students. The researcher used semi-experimental method for the experimental and control groups, where the sample of study consisted of (104) class of the 5th grade randomly selected. The students were divided into two groups: an experimental group of 52 students and a control group of 52 students. The equality of the two groups in mathematical power test were verified. Also, to achieve the goal of the research, the researcher prepared an instrument of mathematical power test and a manual of teaching chapter 3 (multiplication) of 5th grade mathematics book part I based on mental arithmetic. The instrument and the manual were presented to a group of board members for judgment. Then the validity and reliability of the instrument were checked. The result of the study was there are statistically significant differences between the average scores of the experimental group students and the control group students in the post application of mathematical power test in its three dimensions (mathematical communication, mathematical connection, and mathematical reasoning) due to the different teaching strategy used (electronic applications of mental arithmetic – the usual method) for the benefit of the experimental group. Based on the result of the study, the researcher recommended using electronic applications of mental arithmetic in teaching mathematics, as well as converting students’ assessments to mathematical power and training teachers on how to use them and how to develop them.
Keywords: mental arithmetic; mathematical power; primary school student